Professional Burnout in Workers in Nurseries and Kindergartens in a Southern Chilean Province: An Approach to Childrens Mental Health (Global Journal of Human-Social Science, 2021)
In Chile there is little information on professional burnout in workers in nurseries and kindergartens, despite the fact that it is a phenomenon that would have consequences not only for those who suffer from it but also for the people around them, particularly those who are under their care. Methodology: A quantitative approach, descriptive non-experimental transectional design was used. 97 caregivers selected through convenience sampling were studied, to whom the Maslach Burnout Inventory (HSS) and a sociodemographic background scale were applied with the objective of determining the prevalence of burnout syndrome in such workers in a province of the South of Chile. Results: The results show that almost all the participants (99%) have some level of professional burnout, a high number of people have medium or high levels of Emotional Exhaustion (46.9%) and Depersonalization (31.2%), as well as a level medium or low Personal Achievement (27.1%). It was also observed that Emotional Exhaustion varies according to the stage of development (p = .009) and the educational level (p = 0.017).
Keywords: burnout; early childhood educators; child mental health; alternative care